Synthesizing a policy-relevant perspective from the three IPCC "Worlds"—A comparison of topics and frames in the SPMs of the Fifth Assessment Report. (May 2016) - Fløttum, Kjersti; Gasper, Des; St. Clair, Asuncion Lera
Highlights: Framing and linguistic analysis of the IPCC Summaries for policymakers. Summaries for policymakers reflect the different mandates of the three IPCC Workings Groups. The Synthesis Summary for policymakers integrates the 3 worlds identified in the Working Groups Summaries. Risk framing suited to the human side of climate change in the Synthesis Summary. The poorest and weakest people of the world remain near-invisible in all Summaries for policymakers. Abstract: The paper investigates topics, emphases, frames and absences in the Summary for Policymakers parts of the three Working Group reports in the IPCC 5th Assessment Report and the Summary for Policymakers of the Synthesis Report. It explores similarities and differences by using various tools of lexical and discourse analysis, combining quantitative and qualitative methods. The main results are these: First, each Working Group's Summary reflects not only the Working Group's distinctive mandate but also a distinctive intellectual framing. Second, although there are some significant differences in the emphases given to different themes from the Working Groups, the Synthesis Summary covers the main topics of the three other Summaries, and constitutes a relatively integrated summary of the complete Assessment Report. Third, we find though that the Synthesis Summary centrally follows up the risk framing and language which are prominent in Working Group II but semi-absent in the other Working Groups, as part of constructing a policy-relevant statement from the three distinctive reports. In addition, the Synthesis Summary makes use of linguistic devices which contribute to 'amplify' the strength of statements, as part of transferring messages effectively from the scientific context to a policy-maker audience. Fourth, we find that the style and tone of the IPCC Summaries conduce also to important absences and imbalances in emphasis: main victims of climate change (particular groups of vulnerable people) remain virtually invisible in the Summaries, unlike the impacts in nature and ecological systems or the aggregate economic impacts, and correspondingly the challenges, options and opportunities for action remain relatively underdeveloped in the analysis.